When size does matter: organelle size influences the properties of transport mediated by molecular motors - de Rossi, María Cecilia (2013)
Background: Organelle transport is driven by the action of molecular motors. In this work, we studied the dynamics of organelles of different sizes with the aim of understanding the complex relation between organelle motion and microenvironment. Methods: We used single particle tracking to obtain trajectories of melanosomes (pigmented organelles in Xenopus laevis melanophores). In response to certain hormones, melanosomes disperse in the cytoplasm or aggregate in the perinuclear region by the combined action of microtubule and actin motors. Results and conclusions: Melanosome trajectories followed an anomalous diffusion model in which the anomalous diffusion exponent (α) provided information regarding the trajectories' topography and thus of the processes causing it. During aggregation, the directionality of big organelles was higher than that of small organelles and did not depend on the presence of either actin or intermediate filaments (IF). Depolymerization of IF significantly reduced α values of small organelles during aggregation but slightly affect their directionality during dispersion. General significance: Our results could be interpreted considering that the number of copies of active motors increases with organelle size. Transport of big organelles was not influenced by actin or IF during aggregation showing that these organelles are moved processively by the collective action of dynein motors. Also, we found that intermediate filaments enhance the directionality of small organelles suggesting that this network keeps organelles close to the tracks allowing their efficient reattachment. The higher directionality of small organelles during dispersion could be explained considering the better performance of kinesin-2 vs. dynein at the single molecule level.